15‐3: Reflective Liquid Crystal Polarization Volume Grating for SWIR with High Diffraction Efficiency and Large Diffraction Angle and Sensor Application - Hisanaga, Kazuya; Yanai, Yujiro; Saitoh, Yukito; Nagai, Michio; Ito, Yoji (SID International Symposium Digest of technical papers, 2024)
We have developed a reflective polarization volume grating using liquid crystal polymer for SWIR with high efficiency and a large diffraction angle. By using this grating and a lightguide system, we demonstrated a sensor system that can capture identical images simultaneously in both visible and SWIR light.